The Impact of Jigsaw and Window-Shopping Cooperative Learning Models on Students' Social Studies Achievement - Wahyuni, Nur; Elpisah; Hartini (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study evaluates the impact of Jigsaw and Window Shopping cooperative learning models on students' academic achievement. A quantitative approach with a pretest-posttest design without a control group was used. The sample consisted of 12 students selected from the same population. Data were collected through pretest and posttest scores after implementing each learning model. The Jigsaw model resulted in varying impacts on student achievement, while the Window Shopping model had a positive effect on social studies outcomes for Grade VII students. However, no significant differences were observed between the two models. Both demonstrated comparable effectiveness in enhancing student learning within the research context. These results suggest that both models are similarly useful in educational settings.